2021
DOI: 10.7554/elife.69630
|View full text |Cite
|
Sign up to set email alerts
|

How will mosquitoes adapt to climate warming?

Abstract: The potential for adaptive evolution to enable species persistence under a changing climate is one of the most important questions for understanding impacts of future climate change. Climate adaptation may be particularly likely for short-lived ectotherms, including many pest, pathogen, and vector species. For these taxa, estimating climate adaptive potential is critical for accurate predictive modeling and public health preparedness. Here, we demonstrate how a simple theoretical framework used in conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 280 publications
0
42
0
Order By: Relevance
“…Understanding the environmental determinants of Cx. pipiens diversity is important because it can help us predict changes under future climate and land use regimes 91 . It is widely accepted that the geographic distributions of many animals and plants, including mosquitoes, will shift as the planet warms 92,93 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the environmental determinants of Cx. pipiens diversity is important because it can help us predict changes under future climate and land use regimes 91 . It is widely accepted that the geographic distributions of many animals and plants, including mosquitoes, will shift as the planet warms 92,93 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a surge in temperature has shifted timing and length of breeding season in birds (Hällfors et al, 2020), leading to mismatch with optimal resource abundance, which is vital for reproductive success. For short-lived ectotherms, the spread of mosquito species to new habitats in high elevations, short generation times, high population growth rates, and strong temperature-imposed selection could lead to fast adaptation (Couper et al, 2021). In the western Himalayan context, the thermodynamic model showed that the EIP days do not support transmission of avian haemosporidians parasites at high-elevation sites (3200 m).…”
Section: Discussionmentioning
confidence: 99%
“…Similar, temperature-dependent replication rates of different genotypes have been observed among ZIKV strains with African lineage replicating efficiently at both 20°C and 28°C ( 111 ). Since studies have shown that various mutations can support temperature-dependent adaptation of RNA viruses (see “Temperature Impact on Virus Replication, Transcription, and RNA Structure” above) and the short generation times of vectors support adaptation to new environments ( 127 ), it seems likely that when temperatures increase for longer periods of time, RNA viruses will adapt to maintain their transmission rates at elevated temperatures and that overall RNA virus spread over the globe will increase.…”
Section: Migration and Evolution Of Rna Viruses In Response To Temper...mentioning
confidence: 99%